The Concept of Universality Gadamer's Theory of Hermeneutics - Pelton, Sarah (My University, 2005)
Hans-Georg Gadamer's contribution to the philosophical discipline of hermeneutics is clearly acknowledged and has been reflected upon at length, particularly following his publication of Wahrheit und Methode in 1960. However, far less attention has been given to his contributions to hermeneutics in the field of theology. Since it is often thought that Gadamer's concentration on philosophical and historical themes suggests he was deliberately setting himself apart from religious discussions, few scholars have seriously engaged Gadamer's contribution to theological hermeneutics. In this thesis, I am attempting to unify Gadamer's diverse writings on the topic of religion in order to determine where he believes the project of theological hermeneutics ought to be found within the overall scope of hermeneutics as a general discipline. In order to do this, I begin with the division Gadamer establishes between the natural sciences and the human sciences. I draw upon the idea of application - as found in the natural sciences - as well as the concept of historical-linguistic universality - as it emerges from within the human sciences - in order to situate the interpretation of theological texts within Gadamer's framework. I present this account oftheological hermeneutics as one that shares some characteristics of both the natural and the human sciences because of its unique subject of faith. I argue that Gadamer offers an account of theological hermeneutics that is clear and evident, although it does not fit neatly into his original disciplinary division but is instead found at the intersection of the natural and human sciences.
Keywords: Religious Studies; Religion; Religion